Molecular recognition with metal containing supramolecular compounds: Soluble tetradentate dithioglyoximes for the detection of organic solvents in the gas phase - (:unkn) unknown (ELSEVIER SCIENCE SA LAUSANNE, 1996)
A series of soluble tetradentate dithioglyoxime such as mono-, tri- and pentanuclear metal complexes as well as their heteronuclear polymers are investigated as sensitive materials for the detection of organic solvent vapors by utilizing quartz crystal microbalance (QCM) and interdigital capacitor (IDC) as sensor transducers. The results show completely reversible sensor signals even at room temperature with typical response and recovery times in the order of minutes. Layers of the copper trinuclear complex on QCM-devices show the highest mass sensitivity for all solvent molecules, especially for tetrachloroethylene, whereas the layers of nickel mononuclear complex and heteronuclear polymer generally show only small mass sensitivity for alcohol investigated. As usual, the sensitivities of IDC sensors are lower for non-polar solvents, but higher for polar solvents.
Keywords: gas sensors; quartz crystal microbalance; tetradentate dithioglyoximes; QUARTZ-MICROBALANCE; PHTHALOCYANINES; CAPACITANCE; TRANSDUCERS; POLYMERS; SENSORS